Improving resistance to salt stress by endophytic bacteria in winter rape plants - Grineva, Irina A.; Lomonosova, Veronika A.; Maslak, Diana V.; Russkikh, Ivan A.; Sadovskaya, Ludmila E.; Skakun, Tatyana L.; Feklistova, Irina N.; Maksimova, Natalya P. (Experimental Biology and Biotechnology, 2021)
As a result of laboratory experiments to study the induction of systemic resistance in winter rape plants under conditions of salt stress, it was found that treatment of plants with endophytic bacterial strains 12 (isolated from corn grain), R13 (isolated from triticale roots) and 22 (isolated from rye roots) significantly increases the survival rate, length and weight of plant shoots. The selected endophytic strains are promising for the creation of a phytoprotective bacterial biological preparation on their basis.
Keywords: endophytic bacteria; salt stress; systemic resistance; winter rape